Interactive Multimedia Modul as Learning Tool in Biological Science for the Digestive System Topic - Norsham, Mohd. Rafiq (2006)
Information Era and globalization have created new needs for skilled workers in science and technology sector. The government hopes more students especially those entering higher education institute, will learn science and technology. Statistic have shown that the number of science students decrease every year. Studies also have shown that students and teachers have problems in learning and teaching science, which started from schools especially in lower secondary school students that is sitting for the Peperiksaan Menengah Rendah (PMR) examination. A study conducted with help from the Lembaga Peperiksaan Malaysia on PMR examination questions and answers (1993-1999) have shown that students have difficulties answering certain topics during examination. These topics were identified and an interactive multimedia modul with the title ‘Sistem Pencernaan’ (Digestive System) was built using latest multimedia technology softwares. Teaching and learning concepts were carefully implemented to make sure an effective and user friendly module was produced. To test the module’s effectiveness in secondary school, 90 form 2 students from 3 classrooms were selected using randomized block method and they were divided into 3 groups X, Y and Z (control). Each group were given different treatment, either learning using multimedia modul or learning with the help of a science teacher. Test result (correct answers) from each student in the Ujian Pencapaian 1 (Pre-test) and Ujian Pencapaian 2 (Post-test) have been compared statistically using ANOVA method. Statistic test results from Ujian Pencapaian 1 have shown that students using moduls without any help from teachers have significantly (p<0.05) obtained better grades compared to students that have been thaught by teachers. Test results from Ujian Pencapaian 2 shows that students using moduls as revision tools obtained significantly (p<0.05) better gades compared to control students, who did not use the modul at all. The experiment clearly shows that an effective interactive multimedia modul can be used as an important tool for self-learning and revision in schools. Moduls that were produced with good instructional design and teaching techniques are capable to make student learn more and understand problematic topics in science